Adaptations of Breast Imaging Centers to the COVID-19 Pandemic: A Survey of California and Texas. Issue 3 (9th March 2021) - Chalfant, James S; Cohen, Ethan O; Leung, Jessica W T; Pittman, Sarah M; Kothari, Pranay D; Downey, John R; Sohlich, Rita E; Chong, Alice; Grimm, Lars J; Hoyt, Anne C; Ojeda-Fournier, Haydee; Joe, Bonnie N; et al.
Abstract: Objective: To determine the early impact of the COVID-19 pandemic on breast imaging centers in California and Texas and compare regional differences. Methods: An 11-item survey was emailed to American College of Radiology accredited breast imaging facilities in California and Texas in August 2020. A question subset addressed March–April government restrictions on elective services ("during the shutdown" and "after reopening"). Comparisons were made between states with chi-square and Fisher's tests, and timeframes with McNemar's and paired t -tests. Results: There were 54 respondents (54/240, 23%, 26 California, 28 Texas). Imaging volumes fell during the shutdown and remained below pre-pandemic levels after reopening, with reduction in screening greatest (ultrasound 12% of baseline, mammography 13%, MRI 23%), followed by diagnostic MRI (43%), procedures (44%), and diagnostics (45%). California reported higher volumes during the shutdown (procedures, MRI) and after reopening (diagnostics, procedures, MRI) versus Texas ( P = 0.001–0.02). Most screened patients (52/54, 96% symptoms and 42/54, 78% temperatures), and 100% (53/53) modified check-in and check-out. Reading rooms or physician work were altered for social distancing (31/54, 57%). Physician mask (45/48, 94%), gown (15/48, 31%), eyewear (22/48, 46%), and face shield (22/48, 46%) use during procedures increased after reopening versus pre-pandemic ( P < 0.001–0.03). Physician (47/54, 87%) and staff (45/53, 85%) financial impacts were common, but none reported terminations. Conclusion: Breast imaging volumes during the early pandemic fell more severely in Texas than in California. Safety measures and financial impacts on physicians and staff were similar in both states.